Note: Electrochemical cell for in operando X-ray diffraction measurements on a conventional X-ray diffractometer - Hartung, Steffen (2015)
Electrochemical in operando X-ray diffraction (XRD) is a powerful method to analyze structural changes of energy storage materials while inserting/de-inserting charge carriers, such as Li- or Na-ions, into/from a host structure. The design of an XRD in operando cell is presented, which enables the use of thin (6 μm) aluminum foil as X-ray window as a non-toxic alternative to conventional beryllium windows. Owing to the reduced thickness, diffraction patterns and their changes during cycling can be observed with excellent quality, which was demonstrated for two cathode materials for sodium-ion batteries in a half-cell set-up, P2-Na0.7MnO2 and Na2.55V6O16⋅0.6H2O.